School professionals committed to student well-being. Issue 1 (1st January 2021) - Onnela, Anna; Hurtig, Tuula; Ebeling, Hanna
ABSTRACT: The northern provinces of Finland are mostly not densely populated, with long distances to healthcare services. This creates a challenge for how to reach all children and adolescents with mental health services. In order to assess the effectiveness of school-based mental health promotion interventions, it is essential to understand the views of school professionals on student well-being and mental health promotion activity in schools. This study was carried out in urban area comprehensive schools where psychiatric nurses delivered additional mental health promotion interventions. The data were collected using a questionnaire, and a mixed-methods approach was utilised in the analysis. School professionals perceived that students are more unwell than before; they exhibit a general disregard for their well-being and more mental health problems. The respondents regarded the promotion of students' mental health as a basic function of schools. Teachers need adequate support with this work.